Hubungan Model Pembelajaran Picture and Picture Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas VI SD Negeri 030399 Kecamatan Silima Pungga Pungga Kabupaten Dairi Tahun Pembelajaran 2023/2024 - Yohana Eka Indah Napitupulu; Nisma Simorangkir2; Roida Lumbantobing3 (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
The aim of this research is to determine the relationship between the picture and picture learning model on the active learning of Christian Religious Education for class VI students at SD Negeri 030399, Silima Pungga Pungga District, Dairi Regency, Academic Year 2023/2024. Thesis of the Christian Religious Education Study Program with the hypothesis that there is a positive relationship between the picture and picture learning model on the active learning of Christian Religious Education for class VI students at SD Negeri 030399, Silima Pungga Pungga District, Dairi Regency, Academic Year 2023/2024. This research uses descriptive quantitative research methods with a population as well as a research sample of 35 people. The research instrument was a closed questionnaire and was tested on 32 students at SD Negeri 030388 Parongil with a validity test of rcount > rable, namely 0.396 to 0.718 > 0.349, this shows that the entire questionnaire is valid and the reliability test r11 0.874 (0.800 – 1.000) is in the very category strong means the questionnaire is valid and reliable and can be used as a research instrument. From the results of the data analysis, it was obtained that the correlation coefficient (rxy) was 0.396 > 0.334 in a positive direction, meaning that there was a positive relationship between the Picture and Picture Learning Model and the Learning Activeness of Christian Religious Education for Class VI Students at State Elementary School 030399, Silima Pungga Pungga District, Dairi Regency, Academic Year 2023/ 2024. Thus it is concluded that Ho is rejected and Ha is accepted.